Electronic vote in Colombia (2013)
The occurrence of the technology electronic she allows nowadays introduce turnarounds rugged on the running than trials electoral. The biometría electoral he goes of the hand at the implementación of the mechanism than vote electronic the cual consistency on recognize or authenticate fully at the elector oncoming with a document than sameness for vote , she avoids the possible suplantaciones than voters , in as much as the authentication oneself she achieves through the cutlet of the tread dactilar and the information than hay on the charter than citizenship , in addition oneself confronta with the information dactilar of the townsman than she rests on the registries of the Registraduría National of the Been Civil. This Rehearsal he has sort of objective Recognize the result on the presupposed General of the Nation , the implementación of the Vote Electronic on Columbia , based the she finalizes elections effect on Columbia on the year 2010, the cuales to congress cost $193,747,250,451, value than oneself increment if oneself if they were to have realized low the mechanism than vote electronic for $435,361,434,512. The $193,747,250,451 she is source of the Registraduría National of the Been Civil , and $435,361,434,512 they are calculations of the present document , seizing sort of base the information of the Observatory Electoral Latin American , than regard the cost than implementación of the vote electronic on US $ 5 through vote. If on each maquina than ballot he has capacity than attention than 400 voters , ourselves resulta US $ 2,000 through maquina and to top at the age of 30.000.000 than sufragantes of the territory Colombian she'd need maquinas. The previous ourselves livable for conclude , than regardless of the retrenchment on spending than personal of the preconteo habitual and the digitalization of the distinct results electoral and on the spending General sort of tangible , provisions and printed tarjetones , urns than cardboard , formulate than elaboration manual through the sworn and remaining , the cost of the implementación she is really stop and the impact on the presupposed of the Nation logically she is Negative.